2013
DOI: 10.1021/jp4067247
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Reflectivity Reveals a Nonmonotonic Ion-Density Profile Perpendicular to the Surface of ErCl3 Aqueous Solutions

Abstract: Complex interactions that determine ionic ordering in the bulk of electrolyte solutions are modified by surface-region inhomogeneities. We present results from an investigation of surface-ionic profiles that provide insights into the underlying physical chemistry in this region. X-ray reflectivity measurements from the liquid surfaces of aqueous ErCl3 solutions reveal in unprecedented detail a nonmonotonic electron density profile, which is interpreted in terms of a nonmonotonic surface distribution of cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…36 h of scan-upon-scan data collection by measurements and observations of the totally reflected beam intensity and position with a phosphor screen with a digital camera. Surface tension measurements made at the start and at the conclusion of the X-ray absorption experiments are identical to those reported beforehand; 35 the results are diagnostic of a pure and clean electrolyte−He interface.…”
Section: ■ Experimental Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…36 h of scan-upon-scan data collection by measurements and observations of the totally reflected beam intensity and position with a phosphor screen with a digital camera. Surface tension measurements made at the start and at the conclusion of the X-ray absorption experiments are identical to those reported beforehand; 35 the results are diagnostic of a pure and clean electrolyte−He interface.…”
Section: ■ Experimental Methodssupporting
confidence: 77%
“…34 The results showed an upper limit for the Er concentration at the interface that was consistent with a uniform concentration extending from the bulk to the surface. Complementary X-ray reflectivity experiments, which provided subnanometer spatial resolution along the direction perpendicular to the aqueous ErCl 3 electrolyte-vapor surface, showed a nonmonotonic variation of Er concentration in this direction, with a depletion layer at the surface followed by a subsurface enhancement layer, 35 a finding contrary to our initial assumption from a separations perspective but consistent with known negative adsorption behaviors of multivalent cations at an interface. 10,36−42 Both surface depletion and subsurface enrichment of Er 3+ lead to local variations in concentration that can induce different interion orderings in The Journal of Physical Chemistry B Article much the same manner as found in bulk electrolytes of different concentrations.…”
Section: ■ Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The enhancement of ion density near the interface coupled with ion-induced quenching of capillary waves may lead to layering of ions in the direction perpendicular to the interface. Recent X-ray reflectivity experiments have shown layering of erbium chloride at the air-water interface (26).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility that doubly charged Fe 2+ cations might be present in shallow interfacial layers is supported by molecular dynamics calculations, which predict that the concentration of doubly charged Mg 2+ peaks at ∼4 Å below the Gibbs dividing surface at values twice as large as its concentration in bulk water (83). Recent X-ray reflectivity studies confirmed the existence of nonmonotonic cation density profiles within ∼1-nm interfacial layers of aqueous electrolyte solutions (84). We cannot rule out the possibility that impinging gases are hydrated before colliding with the liquid surface (85, 86), but we deem it inconsequential because O 3 -(H 2 O) n and 6 2+ has a distorted octahedral geometry, on account of the broken symmetry, that lets O 3 approach the Fe 2+ center via low-energy associative interchange pathways (88).…”
Section: -10mentioning
confidence: 96%